The construction of semantic waves of knowledge-building: High school students´ natural science writing - Svensson, Birgitta (HERMES - Journal of Language and Communication in Business, 2019)
This paper investigates popular science articles written by Swedish high school students as part of a project aimed at building their knowledge of the content of their natural science curriculum by integrating it with their Swedish language studies. This work, an effort to promote content-area literacy and knowledge-building, was undertaken during their project time. By analyzing the students´ texts, the purpose of the study was to access their value as knowledge-building tools. The analysis of the texts was carried out utilizing Maton´s (2013) theoretical concepts of waves of semantic density and semantic gravity, which are seen as a prerequisite for cumulative knowledge-building. The investigation extends previous studies on semantic waves since it incorporates into the analyses both linguistic features and visual elements. The students were writing in pairs and a total of six texts were analyzed. The text analyses showed three different types of semantic profiles, with four of the texts including features that served as means of cumulative knowledge-building. In a concluding section, some pedagogical implications of the study are considered.